The Relevance of Master Degree Programs in Enhancing Employability in Tanzania: A case of Makete and Mbeya Districts - King, Norman A.S.; King, Jane Edward (Archives of Business Research, 2018)
Education is critical for the development of any countries the world over. In this regard, various levels of education certification have been created for the purpose of improving people’s knowledge and hence be able to master their environment. The levels are many, and include bachelor, master and doctor of philosophy degrees. Irrespective of these various degrees, the paramount question is the extent to which these degree can facilitate employability both self-employment and being employed by second part. This study seeks to find the role of master degree in creating employability. The study utilizes interview, documentation, experiential and observation as the major information collection strategies. The analysis of the findings has used content analysis, which apprehends logical reasoning through systemic thinking. It is a multi- case study design as it incorporates two districts of Mbeya and Makete. 24 workers have been subjected in the study. 11 from Mbeya city council, 9 from Mbeya district council, and 4 from Makete district. The sample has included only workers from each council who hold a master degree. Hence, the total sample was 24. This was 96 percent of the workers with master degree at these councils. Percentiles and relevant analytical tools have been used to provide required information for consumption of the entire world through analysis. The paper concludes that 2% of the interviewed indicated that master degree programs does facilitate self-employment. 12% indicated that master degree does create employment in central and local government. Generally, an average of 26.6% indicated that master degree does create employability, while 73.4% indicated that master degree program does not create employability. We therefore suggest that it is imperative for the turnaround on the programs we teach at university levels for the purpose of providing relevant knowledge which provides answers to the problems we face in our societies and thus enable graduates to have ability for self-employment and or be employed.